Layered Offset Min-Sum Decoding for Low Density Parity Check Codes - Maammar, Nejwa El; Bri, Seddik; Foshi, Jaouad (2018 International Symposium on Advanced Electrical and Communication Technologies (ISAECT), 2018)
Offset Min-Sum Algorithm (OMSA) and Normalized Min-Sum Algorithm (NMSA) are widely used in commercial LDPC decoders due to low complexity and reasonable performance. In this paper we proposes an Adaptive Layered Offset min- sum algorithm for the decoding of LDPC codes, which utilizes an adaptive offset factor to improve the accuracy of the soft information transferred during the iterative decoding process, and it provides good performance accordingly. The performed simulations showed that the layered offset min-sum decoding for LDPC codes can provide significant improvement compared to existing MS based algorithm, OMSA and NMSA.